A Convenient and Efficient Protocol for the Synthesis of 1,3,5-Triaryl-2-pyrazolines in Acetic Acid under Ultrasound Irradiation - Zhi-Ping Lin; Ji-Tai Li (E-Journal of Chemistry)
1,3,5-Triaryl-2-pyrazolines were synthesized in acetic acid in high yields within 60-180 min under ultrasound irradiation at room temperature.